Exploring the compatibility of interspecific grafting and budding methods in propagation of breadfruit (Artocarpus altilis) - S, SURYA; P M, ZAHIDA; RAJU, VISHNU; KRISHNAN, ANU G; PAUL, RESMI (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted during the rainy (kharif) and winter (rabi) seasons of 2023–24 at College of Agriculture, Kerala Agricultural University, Vellanikkara, Kerala to identify suitable vegetative propagation methods and compatible rootstocks for breadfruit [Artocarpus altilis (Parkinson) Fosberg.]. The experiment was laid out in factorial randomized complete block design (F-RCBD) with two factors, namely methods of propagation and types of rootstocks. Patch budding and softwood grafting were tried using one-year-old rootstocks of three different species, such as A. heterophyllus (Jackfruit), A. camansi (Breadnut) and A. hirsutus (Wild jack/Anjili). Success percentage, growth parameters and histological characteristics of budded and grafted plants were evaluated. Results revealed that patch budding was the most suitable propagation method with a success rate of 33.3% in rainy season compared to softwood grafting (3.33%) and A. camansi is more compatible with A. altilis (success rate 38.33%) compared to other two species. Patch budding on A. camansi in rainy season was identified as the superior with a success rate of 66.67% followed by patch budding on A. hirsutus (33.33%) and softwood grafting on A. camansi (10%). In contrast, A. heterophyllus exhibited poor compatibility with A. altilis and failed to produce viable grafted or budded plants, suggesting its incompatibility with breadfruit.